Development of Carbon Based NPK Slow Release Fertilizer using Biochar from Oil Palm Empty Fruits Bunch - Finalis, Era Restu; Sri Djangkung, Sumbogo Murti; Arfiana; Noor, Ilhamsyah; Suratno, Hadi; Rosyadi, Erlan; Saputra, Hens; Noda, Reiji (Purnomo Yusgiantoro Center, 2020)
Biochar is a solid material produced by thermochemical conversion of biomass under oxygen-limited conditions. It has a wide surface and contains many pores so that it can be used as a material for making fertilizer. Biochar based slow release NPK fertilizer was formulated and developed to reduce nutrient leaching and greenhouse gas emissions. In this research, biochar which was a by-product of biomass gasification using oil palm empty fruit bunches was processed to make slow release biochar NPK fertilizer. Sources of nitrogen (N) were derived from urea, phosphate (P) from diamonium phosphate (DAP) and potassium (K) derived from potassium chloride (KCl). Zeolite was added as a matrix to improve fertilizer characteristics. All materials were formulated to make slow release biochar NPK fertilizer used for red onion (Allium sepa) plant applications. Several micronutrients were also added including Mg (MgSO4 fertilizer) and S (ZA fertilizer) to support plant growth. The characterization of fertilizer products was carried out by using SEM, BET etc. to determine physical properties including surface area, pore volume, morphology and composition. Furthermore, biochar NPK fertilizer was applied to the red onion plant which was a high-value crop in Indonesia. The application of NPK biochar fertilizer on red onion plant showed its superiority compared to commercial NPK fertilizers. In addition, the use of Magnesium and sulfur micronutrients could support the growth of red onion bulbs so that they produced more and bigger bulbs.*The paper has been selected from a collaboration with IPST and 7th ICFCHT 2019 for a conference entitled